NAIVE BAYES ALGORITHM IN PREDICT GRADUATION OF STUDENTS - Shedriko, Shedriko (UIN Sumatera Utara, 2019)
Abstract. The University of XYZ is a well established university which has five faculties with one of them is post graduate. Charging with a very low cost of tuition fee has attracted so many high school graduation and make it becoming the university with the bulk number of students. It has caused one subject is taught by more than one lecturer. This research is using quantitative analysis method with Naive Bayes Algorithm methodology in passing decision on PTI (Pengantar Teknologi Informasi) subject. The result gives pattern of training data in mean and standard deviation towards three attributes, i.e. tasks, mid-semester and final exam score, which can classify or predict graduation for new data test. The pattern of this equation can also be used for other class classification, on the same or different subjects.